2018
DOI: 10.15789/2220-7619-2017-4-419-424
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic-Based Sanitation as Alternatives to Chemical Disinfectants

Abstract: Резюме. Известно, что любые поверхности окружающей среды в лечебно-профилактических организациях являются резервуаром для микроорганизмов и способствуют передаче патогенов, увеличивая риск перекрест-ного загрязнения через опосредованный контакт с пациентом. Широкое и не всегда рациональное использо-вание химических дезинфицирующих средств несет риски для безопасности окружающей среды, пациен-та и медицинского персонала. В связи с этим актуальным остается поиск альтернативных методов очистки и обеззараживания а… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These studies consistently observed significant reductions in total pathogen numbers by the first sampling time point (between 1and 4 weeks) with PBS treatment, and this reduction was maintained throughout the duration of the experiments [69,72,73,[77][78][79]84]. Alternatively, no significant variations in pathogen numbers were observed at these same time points with chemical disinfectant treatment [69,72,73,[77][78][79]84]. The largest of these studies, an 18-month study conducted across six Italian hospitals in 2016-2017, reported an 83% decrease in the surface pathogen burden and more than a 50% decrease in the number of HAI-associated microorganisms [73].…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…These studies consistently observed significant reductions in total pathogen numbers by the first sampling time point (between 1and 4 weeks) with PBS treatment, and this reduction was maintained throughout the duration of the experiments [69,72,73,[77][78][79]84]. Alternatively, no significant variations in pathogen numbers were observed at these same time points with chemical disinfectant treatment [69,72,73,[77][78][79]84]. The largest of these studies, an 18-month study conducted across six Italian hospitals in 2016-2017, reported an 83% decrease in the surface pathogen burden and more than a 50% decrease in the number of HAI-associated microorganisms [73].…”
Section: Resultsmentioning
confidence: 82%
“…Remarkably, the majority of in situ hospital studies identified in Table 1 have demonstrated that PBS has led to a stable reduction in the pathogen burden on high-touch hospital surfaces as well as a significant reduction in hospital acquired infections (HAIs) [69,73,78,79]. These studies consistently observed significant reductions in total pathogen numbers by the first sampling time point (between 1and 4 weeks) with PBS treatment, and this reduction was maintained throughout the duration of the experiments [69,72,73,[77][78][79]84]. Alternatively, no significant variations in pathogen numbers were observed at these same time points with chemical disinfectant treatment [69,72,73,[77][78][79]84].…”
Section: Resultsmentioning
confidence: 99%
“…The 32 publications noted in Table 1 ( Falagas and Makris, 2009 ; Manning et al, 2009 ; Kohli, 2013 ; Vandini et al, 2014a , b ; Arvanitakis, 2015 ; La Fauci et al, 2015 ; Caselli et al, 2016 ; Afinogenova et al, 2018 ; Al-Marzooq et al, 2018 , 2019 ; Caselli et al, 2018 ; D'Accolti et al, 2018 , 2019 , 2021 , 2022 , 2023 ; Rodolfi and Caselli, 2018 ; Caselli et al, 2019 ; Dural-Erem et al, 2019 ; Kleintjes et al, 2019 ; Rognoni et al, 2019 ; Caselli and Purificato, 2020 ; Kleintjes et al, 2020 ; Razenberg et al, 2020 ; Stone et al, 2020 ; Tarricone et al, 2020 ; Klassert et al, 2022 ; Soffritti et al, 2022 ; Caselli, 2023 ; Leistner et al, 2023 ; Ramos and Frantz, 2023 ) include an opinion ( Falagas and Makris, 2009 ), two patents ( Manning et al, 2009 ; Rodolfi and Caselli, 2018 ), a commentary ( Caselli and Purificato, 2020 ), a report ( Razenberg et al, 2020 ), two reviews ( D’Accolti et al, 2022 ; Ramos and Frantz, 2023 ), two book chapters ( Kohli, 2013 ; Arvanitakis, 2015 ), three conference abstracts of previously published results ( Al Marzooq et al, 2019 ; Rognoni et al, 2019 ; Caselli, 2023 ), and in vitro assays and hospital-based studies. A total of five publications assessed the efficiency of microbial-based sanitization products using in vitro assays with common healthcare-associated pathogens ( La Fauci et al, 2015 ; D'Accolti et al, 2018 , 2021 ; Dural-Erem et al, 2019 ; Stone et al, 2020 ).…”
Section: Search Strategy and Results Of Literature Overviewmentioning
confidence: 99%
“…A total of 15 publications presented hospital-based studies ( Vandini et al, 2014b ; La Fauci et al, 2015 ; Caselli et al, 2016 , 2018 , 2019 ; Al-Marzooq et al, 2018 ; D'Accolti et al, 2019 , 2023 ; Tarricone et al, 2020 ; Klassert et al, 2022 ; Soffritti et al, 2022 ; Leistner et al, 2023 ). Of these, 7 were multicentric studies ( Vandini et al, 2014b ; Caselli et al, 2018 , 2019 ; Tarricone et al, 2020 ; Klassert et al, 2022 ; D’Accolti et al, 2023 ; Leistner et al, 2023 ) and 8 were monocentric ( La Fauci et al, 2015 ; Caselli et al, 2016 ; Afinogenova et al, 2018 ; Al-Marzooq et al, 2018 ; D'Accolti et al, 2019 ; Kleintjes et al, 2019 , 2020 ; Soffritti et al, 2022 ). One of these publications included an in vitro assay ( La Fauci et al, 2015 ).…”
Section: Search Strategy and Results Of Literature Overviewmentioning
confidence: 99%
“…Sodium hypochlorite disinfection, which comprised any disinfection method specified as bleach or sodium hypochlorite, was identified in 19% of studies [20,44,60 For surface interventions, we found that copper surfaces were in 9% of studies [90,132,152,154,[167][168][169][170][171][172][173][174][175][176][177][178][179]. Other non-copper surface applications or coatings comprised 8% of studies [87,102,[180][181][182][183][184][185][186][187][188][189][190][191][192]. Other non-copper surfaces included coatings incorporating metals such as titanium oxide and silver ions as well as other coatings comprised of polymers, isopropyl alcohol and organofunctional silane, organosilane products, silicon nano-coating inorganic metal and organic quaternary ammonium, silicone quaternary amine, quaternary ammonium silyl oxide, and titanyl oxide moieties.…”
Section: Disinfection Typementioning
confidence: 99%